2020
DOI: 10.3389/fpls.2020.571646
|View full text |Cite
|
Sign up to set email alerts
|

The Seagrass Methylome Is Associated With Variation in Photosynthetic Performance Among Clonal Shoots

Abstract: conservation management of clonal plants should consider epigenetic variation as indicator of resilience and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 146 publications
5
32
0
Order By: Relevance
“…In order not to falsely ascribe improved stress tolerance to the formation of a molecular stress memory, it is critical to distinguish between priming and selection. This could be achieved through establishing correlations between positive priming effects and priming-induced epigenetic shifts that are independent from priming-induced genetic shifts by using partial mantel tests and multivariate redundancy analysis (Foust et al, 2016;Gugger et al, 2016;Herrera et al, 2016;Oksanen et al, 2016;Jueterbock et al, 2020). Moreover, tests for outlier loci that have become dominant allelic variants under positive selection (Narum and Hess, 2011;Günther and Coop, 2013;Ahrens et al, 2018) should be carried out in order to prove that positive priming effects cannot be explained by the survival of adapted genotypes.…”
Section: Discussion -Prospects and Challenges Of Priming In Marine Mamentioning
confidence: 99%
See 1 more Smart Citation
“…In order not to falsely ascribe improved stress tolerance to the formation of a molecular stress memory, it is critical to distinguish between priming and selection. This could be achieved through establishing correlations between positive priming effects and priming-induced epigenetic shifts that are independent from priming-induced genetic shifts by using partial mantel tests and multivariate redundancy analysis (Foust et al, 2016;Gugger et al, 2016;Herrera et al, 2016;Oksanen et al, 2016;Jueterbock et al, 2020). Moreover, tests for outlier loci that have become dominant allelic variants under positive selection (Narum and Hess, 2011;Günther and Coop, 2013;Ahrens et al, 2018) should be carried out in order to prove that positive priming effects cannot be explained by the survival of adapted genotypes.…”
Section: Discussion -Prospects and Challenges Of Priming In Marine Mamentioning
confidence: 99%
“…Evidence that epigenetic modifications contribute to form a thermal stress memory in seagrass is suggested by significant stress-induced regulation of methylation-related genes, in particular histone methyltransferases (Nguyen et al, 2020), and a change in DNA-methylation patterns that lasted for at least 5 weeks following exposure to heat stress (Jueterbock et al, 2020). A 5-week heat-stress memory is potentially long enough to heatharden the same generation of previously exposed shoots.…”
mentioning
confidence: 99%
“…P. oceanica cold-plants not only changed DNA methylation levels during the warming exposure, but they also showed the modulation of genes involved in epigenetic processes commonly used by plants for the transcriptional stimulation of stress tolerance and flowering as a possible mechanism to survive and optimize reproductive success under stress conditions 85 . A very recent paper showed that the methylome of the seagrass Z. marina is flexible and responds directly to environmental changes induced by plant cultured under laboratory conditions and to heat stress 61 . Authors suggest that the co-variation in DNA methylation and photosynthetic performance may be linked via gene expression because methylation patterns varied in functionally relevant genes involved in photosynthesis, and in the repair and prevention of heat-induced protein damage.…”
Section: Cold-plants W Arm-plants Cold-plants W Arm-plantsmentioning
confidence: 99%
“…Variation in DNA methylation has also been correlated to habitat types and shifts in species range (Xie et al 2015;Foust et al 2016;Jueterbock et al 2020). As both a regulator of gene expression and a modification resulting from gene expression (Aceituno et al 2008, Zhang et al 2018, environmentally induced changes in DNA methylation may be indicative of phenotypic plasticity, which can provide a source of variation when there is little genetic variation (Richards et al 2012;Liebl et al 2013;Jueterbock et al 2020). Phenotypic plasticity may be particularly important for rapid response of invasive species to novel habitats (Richards et al 2006 In previous work, we measured the phenotypic and genotypic variation from several populations of invasive Japanese knotweed (Reynoutria japonica and R. x bohemica).…”
Section: Introductionmentioning
confidence: 99%